Avoidance Behavior Is an Independent Indicator of Poorer On-road Driving Skills in Older Adults. (15th May 2019) - Schulz, Philipp; Beblo, Thomas; Spannhorst, Stefan; Labudda, Kirsten; Wagner, Thomas; Bertke, Volkmar; Boedeker, Sebastian; Driessen, Martin; Kreisel, Stefan H; Toepper, Max
Abstract: Objectives: The aim of the current work was to investigate the relationship between avoidance of specific driving situations and on-road driving skills in older drivers considering factors found to be related to both avoidance behavior and driving skills. Method: Seventy-two older drivers ( M = 76 years) from the general population were included in this study. Self-reported avoidance behavior, driving practice, perceived driving difficulties, driving-related cognitive functions, as well as medical conditions were assessed within two sessions. Standardized on-road assessments served for assessing on-road driving skills in a third session. Results: Self-reported avoidance behavior was associated with reduced driving skills ( r = −.41), and this relationship remained significant beyond the influence of cognitive skills, self-reported health, driving practice, and perceived driving difficulties. Specifically, avoidance of driving in bad weather, poor visibility and complicated parking was found to be associated with reduced driving skills. Discussion: This study suggest that avoidance behavior is an independent indicator of impaired driving skills in older drivers. Our results argue against the assumption that avoidance behavior may be a reasonable strategy for safe traffic participation. Longitudinal studies are urgently needed to get more evidence on safety aspects of avoidance behavior.